Aplicação de métodos de projeto no desenvolvimento de carrocerias de ônibus : um estudo de caso - Quevedo, Dionatan Brizola (2014)
Due to the great importance of develop a product at the right time and that catches the commerce interests, becomes necessary the deployment of an effective procedure for good solutions conception. The present thesis has the objective of selecting tools and methods to suggest a design procedure in a bus body development and apply it at the Engineering department in a bus factory. The case study is performed in a Double Decker body, road coach bus, which has the necessity of developing a modular design that provides a shorter time for the layout required by the customer and further an easy assembly on the production line, adapting the company working tools to accomplish the methods, since the planning and initial concept, until the final detailing. This concepts brings a new suggestion for the bus design, where the main structure is not influenced by the chassis and the customer options, offering a standard and flexible body, which can be assembled over the three main chassis models of the category. A prototype approved the configurations. This thesis evaluated the impact of the methods proposed above the results in the categories of standardization, design development time, design assertiveness, product quality, manufacture and assembly body process.